2023
DOI: 10.3389/fsurg.2022.1086877
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic abdominal drainage following appendectomy for complicated appendicitis: A meta-analysis

Abstract: BackgroundTo date, the value of prophylactic abdominal drainage (AD) following appendectomy in patients with complicated appendicitis (CA), including adults and children, has yet to be determined. This paper presents a meta-analysis of the effects of prophylactic AD on postoperative complications in patients with CA, with the goal of exploring the safety and effectiveness of prophylactic AD.MethodsPubMed, Science Direct, Web of Science, Cochrane Library, and Embase databases were searched for relevant articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(183 reference statements)
0
0
0
Order By: Relevance
“…Preoperative mechanical bowel preparation can also increase the loss of intestinal fluid, so we should avoid unnecessary bowel preparation; No catheter before an operation and no drainage tube during the operation can reduce the discomfort and pain of children, which is conducive to getting out of bed early (18). In addition, indwelling abdominal drainage tubes may also increase complications such as incision infection and small intestinal obstruction (19). ( 2) Intraoperative: Control fluid velocity and intake, develop personalized fluid replacement plans.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative mechanical bowel preparation can also increase the loss of intestinal fluid, so we should avoid unnecessary bowel preparation; No catheter before an operation and no drainage tube during the operation can reduce the discomfort and pain of children, which is conducive to getting out of bed early (18). In addition, indwelling abdominal drainage tubes may also increase complications such as incision infection and small intestinal obstruction (19). ( 2) Intraoperative: Control fluid velocity and intake, develop personalized fluid replacement plans.…”
Section: Discussionmentioning
confidence: 99%
“…Appendectomy for complicated appendicitis: A meta-analysis investigated the effects of prophylactic abdominal drainage on postoperative complications in patients with complicated appendicitis. The analysis revealed that drains did not significantly reduce the risk of postoperative complications, providing insight into the limited impact of drain insertion in this specific surgical context [ 27 ].…”
Section: Reviewmentioning
confidence: 99%